Efeito de um sistema de um cultivo em aleias em diferentes consórcios de leguminosas arbóreas sobre grupos de artrópodes - Oliveira, Natália Nicolle Furtado Costa de (2013)
The soil macrofauna plays an important role in the transformation of organic matter added by pruning of legume trees in agroforestry systems. This study evaluated the influence of agroforestry in a demonstration unit of APS's on the macrofauna, identifying the occurrence of its major taxonomic groups in the school farm UEMA, Sao Luis / MA. The system Agroforestry (SAF's) study consists of leguminous trees that form the design of the agroecosystem, resulting in the following treatments: T1: control, T2. Inga (Inga edulis Mart.), T3. Sombrero (fairchildiana RA Howard); T4. Leucaena (Leucaena leucocephala (Lam.) R. de Wit.), T5. Inga + Sombrero, T6. Inga + Leucena and T7. Sombreiro + Leucena and short cycle crop squash (Cucurbita) that was deployed on the streets of agroforestry system in the period from April to December 2011. To collect arthropods were installed 10 traps like "Pitfall" for treatment, distributed in zig-zag between the pumpkin plants. These traps consisted of plastic cups 500ml, containing 400ml of water. The traps were kept for 48 hours field, repeating the procedure every 15 days for nine months. We found a total of 16,485 individuals, and the treatment T6 (Inga + Leucena) was the combination with the highest number of arthropods during the study period (3,894 individuals), followed by treatment T7 (+ sombrero leucaena) with 2825 individuals. The use of cover crops in no-till system provides conditions for the restoration of the invertebrate macrofauna community of the soil resulting in benefits for soil nutrient replenishment. Legumes and contribute to the enrichment of the soil macrofauna, represent promising alternatives to good management of crops and improve soil fertility